Combined effects of dissolved humic acids and tourmaline on the accumulation of 2, 2′, 4, 4′, 5, 5′- hexabrominated diphenyl ether (BDE-153) in Lactuca sativa. (December 2017) - Wang, Cuiping; Ma, Chuanxin; Jia, Weili; Wang, Dong; Sun, Hongwen; Xing, Baoshan
Abstract: In order to investigate the effects of dissolved humic acid (DHA) and tourmaline on uptake of 2, 2′, 4, 4′, 5, 5′- hexabrominated diphenyl ether (BDE-153) by Lactuca sativa, different fractions of DHA, including DHA1 and DHA4, as well as different doses of tourmaline were introduced into BDE-153 contaminated solutions for plant growth. The levels of BDE-153 in L. sativa tissues were positively correlated with the Fe levels ( R 2  = 0.9264) in seedings of the treatments with different doses of tourmaline. However, when adding DHA1 and DHA4 into the system, the correlation coefficients ( R 2 ) decreased to 0.6976 and 0.5451 from 0.9264, respectively. In contrast with the Fe contents, the presence of DHAs didn't affect the R 2 between the levels of BDE-153 and the lipid contents in plant tissues. Our results indicated that both DHA1 and DHA4 could severely alter the BDE-153 uptake by L. sativa through reducing the Fe uptake instead of the lipid contents. Additionally, DHA4 exhibited much stronger abilities to alter the BDE-153 accumulation than DHA1 . Transmission electron microscopy (TEM) observations indicated that either DHA1 or tourmaline or co-treatment with DHA and tourmaline had no negative impact on L. sativa at the cellular level. The present study provides important information for the impacts of different fractions of DHA extracted from soil on the BDE-153 migration in plant systems. Moreover, we elucidated the importance of the iron in tourmaline for migration of the polybrominated diphenyl ethers (PBDEs) in plant systems. Graphical abstract: Highlights: BDE-153 levels in L. sativa tissues positively correlated with Fe levels in seedings. DHA1 and DHA4 decreased correlation coefficients between BDE-153 and Fe levels. DHAs decreased correlation coefficients between BDE-153 levels and lipid contents. DHA4 exhibited much stronger abilities to alter the BDE-153 accumulation than DHA1 . Either DHA1 or tourmaline had no negative impact on L. sativa at the cellular level. Abstract : DHA4 exhibited much stronger abilities to alter the BDE-153 accumulation than DHA1 . The levels of BDE-153 in L. sativa tissues were positively correlated with the Fe levels ( R 2  = 0.9264) in seedings.